1980
DOI: 10.1083/jcb.87.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and utilization of mRNA by myogenic cells in culture.

Abstract: Primary chick myoblast cultures demonstrate the ability to take up exogenously supplied polyadenylated RNA and express the encoded information in a specific manner . This expression is shown to exhibit tissue specificity . Analysis of creatine kinase activity monitored at various times of incubation in the presence of either polyadenylated or nonpolyadenylated RNA indicates that only the poly(A) + mRNA is capable of being actively translated . Radioactively labled poly(A)+ mRNA is taken up by the cell cultures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…These experiments suggest that HAF has a discriminatory role in the intact cell . The fact that MHC-mRNA, inserted in myoblasts in the presence of HAF, was translated with a similar efficiency as previously observed in myotube cell cultures (17) suggests that HAF is a developmentally programmed regulatory protein appearing during myogenesis . These experiments lend strong support to our previous in vitro studies, suggesting that mRNA discriminatory elements play a significant role in the cytoplasmic utilization of mRNAs during muscle differentiation.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…These experiments suggest that HAF has a discriminatory role in the intact cell . The fact that MHC-mRNA, inserted in myoblasts in the presence of HAF, was translated with a similar efficiency as previously observed in myotube cell cultures (17) suggests that HAF is a developmentally programmed regulatory protein appearing during myogenesis . These experiments lend strong support to our previous in vitro studies, suggesting that mRNA discriminatory elements play a significant role in the cytoplasmic utilization of mRNAs during muscle differentiation.…”
Section: Discussionsupporting
confidence: 61%
“…In this case, 24-h dividing myoblast cell cultures were used, as it is known that they contain little if any MHC-mRNA . In addition, we have demonstrated previously that MHC-mRNA can be translated in these cells, but much less efficiently than in differentiated myotubes (17). The position of [3H]MHC-mRNA when delivered alone and after preincubation with the HAF is displayed in Fig .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of the cells to take up and to correctly translate exogenously supplied mRNA had already been demonstrated in a critical review by Mroczkowski et al [28] of myoblast culture data. Somite induction in the presence of actinomycin D and its absence in the pres ence of puromycin in our experiments seems to indicate that translation of mRNA also occurs in our explants.…”
Section: Discussionmentioning
confidence: 99%
“…RNA release from eukaryote cells has been demonstrated 48, 57–68. In initial studies, macromolecular RNA was shown to pass between 3T3 cells in vitro 57.…”
Section: Introductionmentioning
confidence: 99%